PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN PADA PT. BPR PRISMA DANA MANADO - CIPTA JAYA TAHUNA; Sandra Asaloei (JURNAL ADMINISTRASI BISNIS, 2017)
The purpose of this paper is to determine the effect of Emotional Intelligence onEmployee Performance at PT. BPR Prisma Dana Manado. Samples were taken by 50respondents. Data collection method used in this research is questionnaire and observation. Themethod used in this research is quantitative descriptive method, with the approach betweensimple correlation and multiple linear regression to measure the relationship between variables.In this study obtained the results of correlation coefficient calculations showing the relationshipbetween emotional intelligence and strong employee performance is also known coefficient ofdetermination or R Squere which explains the magnitude of the effect of emotional intelligenceon employee performance. R Square value can be interpreted that the influence of emotionalintelligence on employee performance, while the rest influenced by other variables not examinedin this study. The conclusion of this research is basically the employee's performance is good,but it is better for an employee to improve performance in performing every task andresponsibility by understanding emotional intelligence, because this can impact on theimprovement of employee performance quality so that it can have good impact also on progresscompany.